Horace H. Lurton papers - Lurton, Horace H. (Horace Harmon), 1844-1914.
Correspondence and telegrams, some written while Lurton was attending the University of Chicago and while he was a Confederate prisoner in Camp Chase, Ohio, and at Johnson Island Prison during the Civil War. Also includes the draft of an address and printed matter. Correspondents include A.W.B. Allen, of Bridgeford & Co., Louisville, Ky., William R. Day, John Marshall Harlan, Joseph Rucker Lamar, Whitelaw Reid, Theodore Roosevelt, Elihu Root, William H. Taft, and Edward Douglass White.
Associate justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, A. W. B. -- Correspondence; Day, William R. -- 1849-1923 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; Lamar, Joseph Rucker, -- 1857-1916 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; White, Edward Douglass, -- 1845-1921 -- Correspondence; United States. -- Supreme Court; Bridgeford & Co; Johnson Island Prison; University of Chicago (1857-1886); Universities and colleges -- Illinois -- Chicago; Camp Chase (Ohio); Illinois -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Ohio -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865.; Jurists